Major mergers are not significant drivers of star formation or morphological transformation around the epoch of peak cosmic star formation - Lofthouse, E.K.; Kaviraj, S.; Conselice, Christopher J.; Mortlock, A.; Hartley, W. (Oxford University Press, 2017)
We investigate the contribution of major mergers (mass ratios > 1:5) to stellar mass growth and morphological transformations around the epoch of peak cosmic star formation (z ~ 2). We visually classify a complete sample of massive (M > 1010M_) galaxies at this epoch, drawn from the CANDELS survey, into late-type galaxies, major mergers, spheroids and disturbed spheroids which show morphological disturbances. Given recent simulation work, which indicates that recent (<0.3-0.4 Gyr) major-merger remnants exhibit clear tidal features in such images, we use the fraction of disturbed spheroids to probe the role of major mergers in driving morphological transformations. The percentage of blue spheroids (i.e. with ongoing star formation) that show morphological disturbances is only 21 +- 4 per cent, indicating that major mergers are not the dominant mechanism for spheroid creation at z ~ 2 - other processes, such as minor mergers or cold accretion are likely to be the main drivers of this process. We also use the rest-frame U-band luminosity as a proxy for star formation to show that only a small fraction of the star formation budget (~3 per cent) is triggered by major mergers. Taken together, our results show that major mergers are not significant drivers of galaxy evolution at z ~ 2.